Socializing the PLP II Program to Supervising Teachers by Online - Bistari Bistari; Hamdani Hamdani; Rustam Rustam; Zubaidah Zubaidah; Siti Halidjah; Dona Fitriawan (JPKM (Jurnal Pengabdian Kepada Masyarakat) UNTAN, 2021)
Regarding the lecture activities during the covid period, the direct impact and the effect of not doing much were lectures that involved other parties in the field. One of the lecture activities in School Field Practice, PLP II, is previously known as PLP II (Field Experience Practice). Lecture activities from PLP II involve many people. If you pay attention to these conditions, you need an alternative activity to create conducive activities. Problem-solving to achieve activity targets is carried out with online workshops. The form of activity carried out during the Covid pandemic as it is today is webinars. To carry out these activities, the following stages of problem-solving activities are carried out, namely: (1) preparation, (2) implementation, and (3) reporting. Based on the explanation of the results of the data above, it can be concluded as follows: (1) The preparations carried out in the committee are classified as orderly and tend to be in accordance with the targeted plan. It is indicated from the targets to be achieved that run smoothly; and (2) the process of activities carried out is classified as achieving the expected target, considering that most of the targeted targets are in accordance with the direction and purpose.